Family Planning Services by Midwifery of Private Midwifery Practice in Yogyakarta During the Pandemic Period Of Covid-19 - Dian Herawati; Dina Fitriana Rosyada; Rita Dian Pratiwi; Estri Neni Wigati (Faculty of Public Health, Sriwijaya University, 2020)
Covid-19 has been declared a world pandemic by WHO. Large-scale social restrictions and community appeal to stay at home in an effort to oppose Covid-19 transmission will have an impact on the sustainability of family planning services. 54,6% of the total family services planned by midwives are conducted at the private midwifery practice. The purpose of this study was to analyze family planning service visits at the private midwifery practice in Yogyakarta. This study used quantitative descriptive method. The sample in this study is midwives who have private midwifery practice in the Special Region of Yogyakarta. The results showed that almost methods of contraception experienced a decrease in service in the private midwifery practice, except progestin injection. As many as 44,7% of midwives provide family services planned through the post placenta Intrauterine Device (IUD) was a method of contraception that was added as a post partum contraception during the main Covid-19 pandemic. Family service protocols have been implemented in the pandemic era with 19% 78% of midwives, online, and using standard personal protective equipment. There was a decrease in family planning services by midwives in the practice of independent midwives in Yogyakarta during the Covid-19 pandemic by 13,8% (from February to April 2020). By the decline predicted to result in a high chance of a baby boom. Midwives are expected to improve family planning services after delivery, especially the IUD, and utilize online media. Other efforts can be made through the BKKBN, namely by encouraging postpone pregnant during the Covid-19 pandemic and the existence of free family planning services so that productive partners can routinely control the use of acceptors.